METHODOLOGY OF USING GYMNASTICS EXERCISES IN DEVELOPING BALANCE IN YOUNG ATHLETES - Khamroyev Behruz Khalimovich (International Journal of Literature and Language Studies, 2026)
This article analyzes the theoretical and practical aspects of the methodology of using gymnastic exercises in developing balance skills in young athletes. The ability to maintain balance in sports activities is an important component of movement coordination, which plays an important role in ensuring the athlete's accuracy, speed and physical stability of movement. Especially, developing balance in young athletes from an early age is an important pedagogical factor for increasing their physical fitness, correct execution of complex movement elements, and improving sports results. The article emphasizes the importance of selecting gymnastic exercises taking into account the age and individual characteristics of young athletes, gradually increasing the load, and using effective pedagogical methods in the training process. The results of the study show that the systematic and targeted use of gymnastic exercises is an effective tool for developing balance, improving coordination of movements, and increasing the level of physical fitness in young athletes.